The Environmental Benefits Mapping and Analysis Program – Community Edition (BenMAP–CE): A tool to estimate the health and economic benefits of reducing air pollution. (June 2018) - Sacks, Jason D.; Lloyd, Jennifer M.; Zhu, Yun; Anderton, Jim; Jang, Carey J.; Hubbell, Bryan; Fann, Neal
Abstract: A number of software tools exist to estimate the health and economic impacts associated with air quality changes. Over the past 15 years, the U.S. Environmental Protection Agency and its partners invested substantial time and resources in developing the Environmental Benefits Mapping and Analysis Program – Community Edition (BenMAP–CE). BenMAP–CE is a publicly available, PC-based open source software program that can be configured to conduct health impact assessments to inform air quality policies anywhere in the world. The developers coded the platform in C# and made the source code available in GitHub, with the goal of building a collaborative relationship with programmers with expertise in other environmental modeling programs. The team recently improved the BenMAP–CE user experience and incorporated new features, while also building a cadre of analysts and BenMAP–CE training instructors in Latin America and Southeast Asia. Highlights: BenMAP–CE is an open source software program developed in C#. The health and economic benefits of improved air quality can be assessed in BenMAP–CE. BenMAP–CE has been used worldwide in conducting health impact assessments.